The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3389/fnhum.2022.1061668
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Alzheimer's disease using prefrontal resting-state functional near-infrared spectroscopy

Abstract: IntroductionAlzheimer's disease (AD) is neurodegenerative dementia that causes neurovascular dysfunction and cognitive impairment. Currently, 50 million people live with dementia worldwide, and there are nearly 10 million new cases every year. There is a need for relatively less costly and more objective methods of screening and early diagnosis.MethodsFunctional near-infrared spectroscopy (fNIRS) systems are a promising solution for the early Detection of AD. For a practical clinically relevant system, a small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
0
0
Order By: Relevance
“…Notably, fNIRS has the distinct advantage of being administered directly at a patient's bedside, enabling measurement of both neonatal (Mitra et al, 2020;Tang et al, 2024) and adult populations (Bicciato et al, 2022) within the intensive care unit. In addition, fNIRS has been used to measure neural activity in patients with neurodegenerative diseases in scenarios where fMRI is impractical or potentially detrimental, including amyotrophic lateral sclerosis (Kuruvilla et al, 2013), Alzheimer's disease (Blum et al, 2022;Keles et al, 2022), and in chronic disorders of consciousness patients (Abdalmalak et al, 2020). Future studies should consider having these patients watch or listen to movie narratives, as it enables the further exploration of higher-order cognitive processes with minimal time and effort.…”
Section: Taken Vs Taken Scrambled Classificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, fNIRS has the distinct advantage of being administered directly at a patient's bedside, enabling measurement of both neonatal (Mitra et al, 2020;Tang et al, 2024) and adult populations (Bicciato et al, 2022) within the intensive care unit. In addition, fNIRS has been used to measure neural activity in patients with neurodegenerative diseases in scenarios where fMRI is impractical or potentially detrimental, including amyotrophic lateral sclerosis (Kuruvilla et al, 2013), Alzheimer's disease (Blum et al, 2022;Keles et al, 2022), and in chronic disorders of consciousness patients (Abdalmalak et al, 2020). Future studies should consider having these patients watch or listen to movie narratives, as it enables the further exploration of higher-order cognitive processes with minimal time and effort.…”
Section: Taken Vs Taken Scrambled Classificationmentioning
confidence: 99%
“…Owing to its main features, such as affordability, portability, and versatility, fNIRS holds great potential to be applied to pediatric and neonatal (Peng & Hou, 2021;Tang et al, 2024), neurodegenerative (Blum et al, 2022;Kuruvilla et al, 2013;Keles et al, 2022), and critically brain-injured (Abdalmalak et al, 2020;Bicciato et al, 2022;Wang et al, 2022;Shu et al, 2023) populations, as well as naturalistic paradigms more broadly (see Pinti et al, 2018 for a review).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have reported changes in resting cerebral oxygenation levels, fluctuations, or connectivity in patients with Alzheimer's and Mild cognitive impairment 26 . A recent study has shown that fNIRS is a suitable technology for detecting AD and monitoring its progression 27 .…”
Section: Introductionmentioning
confidence: 99%